Satyam Fraud: A Structural Functional Approach to Corporate Governance Reform - Mark Lokanan (Journal of Corporate Governance Research, 2024)
The paper uses Satyam Computer Services Limited as a prototypical case of corporate governance failure and recommendations for reforms. In making recommendations for corporate governance best practices, the paper analyzes Satyam’s corporate governance framework and management controls through a structural functionalist lens. The case is based on materials obtained from the news and print media, published articles, and interviews given by experts who commented on the case. Corporate governance data were obtained from the Securities and Exchange Commission’s (SEC) Edgar database. The findings suggest that corporate governance best practices should not be separate from the discrete parts of the organization. A wider context that encapsulates socio-cultural factors must not only be part of corporate governance mandates; but, also integral in the operational logistic of the corporation. As part of this discussion, the paper explicitly reviewed the governance structure and the make-up of the board of directors that were in place at Satyam prior to the resignation of Chairman Ramalinga Raju and his admission that he was involved in financial statement irregularities. Particular emphasis was placed on how management control systems and cultural controls in companies can shape corporate governance mandates to build effective governance framework.